The Reality On Application And Challenges Of Closed-circuit Television (cctv) Images As Evidence In Shariah Criminal Cases In Malaysia - Wan Abdul Fattah Wan Ismail; Syahirah Abdul Shukor; Hasnizam Hashim; Lukman Abdul Mutalib; Ahmad Syukran Baharuddin (GIAP Journal, 2024)
Indexed by SCOPUS